Absorbing risk : an examination of health and safety policy and practice of survey workers in two New Zealand market research organisations : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy at Massey University - Campbell, Jacquelyn Ann (Massey University, 2002)
This qualitative enquiry explores the health and safety issues of survey workers in New Zealand. There is a dearth of literature concerning the acceptance and absorption of risk in this work environment; this thesis discusses the extent to which these workers both recognise and absorb risks inherent in their occupation. It presents a study of survey workers from two national organisations fictitiously named OpinionQuest and MarketMatrix. Who are these people who knock on doors and phone for our opinions? Are there significant hazards, and are survey workers aware of these? Analysis of the data suggests that survey workers recognise some obvious risks such as dogs and verbal abuse. Yet, many are ill prepared for less predictable dangers, whether from attempted assault, overt sexual overtures, or the road washing away. Recommendations emerging from the research relate to the provision of cellphones; systems for tracking the whereabouts of employees working in the field; and adequate coverage, in training, of the full range of risks that survey workers may encounter. Survey workers are pivotal to the success of their organisations. Without them, the entire process would cease to function.
Keywords: New Zealand; Industrial safety; Industrial hygiene